Quantitative evaluation of the reservoir potential and controlling factors of semi-deep lacustrine tempestites in the Eocene Lijin Sag of the Bohai Bay Basin, East China. (November 2016) - Wang, Junhui; Jiang, Zaixing; Zhang, Yuanfu; Wei, Xiaojie; Wang, Hang; Liu, Shengqian
Abstract: Ancient lacustrine storm-deposits that act as petroleum reservoirs are seldom reported. The Lijin Sag, which is located in the southeastern corner of the Bohai Bay Basin in East China, is a NE–SW trending Cenozoic half-graben basin. Some of its Eocene deposits (Bindong deposits) were interpreted as lacustrine tempestites. The Bindong tempestites, which developed in the lower part of the upper fourth member of the Shahejie Formation (Es4 1 ), constitute a new kind of petroleum reservoir and are novel petroleum exploration targets in the Bindong Area. However, the characteristics of the Es4 1 Bindong tempestite reservoirs and their controlling factors are poorly understood. Point-count analyses of thin sections, scanning electron microscope image analyses, X-ray diffractometry data, and the petrophysical parameters of the Bindong tempestite reservoirs were utilized to estimate the reservoir quality. The reservoirs have undergone significant diagenetic alteration, which can be divided into negative and positive aspects. The negative alteration includes compaction, authigenic minerals, and cementation such as carbonates, clay minerals and overgrowths of quartz and feldspar. The uneven distribution of carbonate cement increased the reservoir's heterogeneity, with carbonate cement commonly precipitating along the sandstone-mudstone contacts. The primary porosity was severely reduced because of compaction and extensive carbonate cementation. Positive alteration includes dissolution, carbonate cementation, undercompaction and fractures. Carbonate cementation exhibited both positive and negative effects on the reservoir quality. Overall, the objective reservoir quality is quite poor. A quantitative evaluation of the reservoirs' potential was conducted. The cutoff values of several of the reservoir's parameters were calculated. The lower limits of the porosity and permeability are 8.35–5.85% and 1.2587–0.2753 × 10 –3 μm 2, respectively, depending on the depth. The upper limits of the carbonate and mud content are approximately 18.5% and 9–10%, respectively. A fundamental understanding of these characteristics will provide necessary information for extracting hydrocarbons from analogous subsurface reservoirs. Highlights: Ancient lacustrine storm-deposits make a kind of petroleum reservoir in Lijin Sag. Compaction and cementation are main causes to destroy reservoir qualities. Dissolution and undercompaction make reservoirs better. The lower limit of porosity and permeability are 8.35–5.85% and 1.2587–0.2753 mD. The upper limit of carbonate and mud content are ∼18.5% and ∼9–10%, respectively.